Body weight cutoff for daily dosage of efavirenz and 60-week efficacy of efavirenz-based regimen in human immunodeficiency virus and tuberculosis coinfected patients receiving rifampin - Weerawat Manosuthi (2018)
Seventy-one human immunodeficiency virus-infected patients with tuberculosis who were receiving a rifampin (rifampicin)-containing regimen were initiated on treatment with efavirenz at 600 mg/day plus stavudine-lamivudine. Fasting efavirenz concentrations at 12 h after dosing (C12) were monitored. The mean ± standard deviation efavirenz C12 at weeks 6 and 12 and after rifampin discontinuation were 4.5 ± 4.3, 3.8 ± 3.5, and 3.5 ± 2.7 mg/liter, respectively. High body weight was associated with a low efavirenz C12 at weeks 6 and 12 (P = 0.003, r = -0.255). The efavirenz C12 regression prediction line at 1 mg/liter intercepted a mean body weight of 57.5 kg. Copyright © 2009, American Society for Microbiology. All Rights Reserved.